UMUMTA’LIM MAKTABLARI IJTIMOIY-PEDAGOGIK TIZIM SIFATIDA: IJTIMOIY FUNKSIYALARI VA DOLZARB VAZIFALARI (Qoraqalpog‘iston Respublikasi misolida) - Tolegenov, M.E. (SCIENCE and SOCIETY, 2023)
In this article, the general education school is studied as a socio-pedagogical system. In addition, their social functions and current tasks were studied on the example of the Republic of Karakalpakstan.
Keywords: education; schools; Republic of Karakalpakstan; Law on Education; outlook; personality; socialization; social function; formation; task